Determination of multiple toxins in whelk and clam samples collected from the Chukchi and Bering seas. (January 2016) - Li, Aifeng; Chen, Huidan; Qiu, Jiangbing; Lin, Heshan; Gu, Haifeng
Abstract: Buccinidae whelk Neptunea varicifera (Dall), Cardiidae clam Serripes laperousii (Deshayes), and two unknown species of whelk and clam were collected from the Arctic Chukchi Sea and sub-Arctic Bering Sea in July 2014. In this study, the mollusk samples were analyzed by different liquid chromatography-tandem quadrupole mass spectrometry (LC-MS/MS) methods for multiple shellfish toxins, including okadaic acid (OA), pectenotoxin (PTX), yessotoxin (YTX), azaspiracid (AZA), cyclic imines (CI), and saxitoxin (STX) groups. PTX2 (≈2.0 μg kg −1 whole tissues) was detected exclusively in the clam S. laperousii collected from the Chukchi Sea. OA and dinophysistoxin-1 (DTX1) were restricted to mollusk samples collected from the Bering Sea, and OA was the dominant component of the whelk N. varicifera (63 μg kg −1 digestive gland) and an unknown species of whelk (6.8 μg kg −1 digestive gland). Spirolide-1 (SPX1) was confirmed in most samples except for the whelk N. varicifera collected from the Bering Sea. The highest content of SPX1 (≈18.5 μg kg −1 digestive gland) occurred in the whelk N. varicifera collected from the Chukchi Sea, along with the suspected presence of SPX-C, SPX-D and didesMe-SPX-C. YTX, as well as its derivatives 45-OH-YTX and 45, 46, 47-Trinor-YTX, were found in all samples, with the highest YTX content (66 μg kg −1 digestive gland) present in the whelk N. varicifera collected from the Chukchi Sea. Interestingly, STX and dcSTX were measured only in the whelk N. varicifera and unknown species of clam collected from the Chukchi Sea. No AZA-group toxins, gymnodimine (GYM), or pinnatoxin G were found in any samples analyzed. Results demonstrated that the mollusk samples were contaminated by multiple shellfish toxins in the Chukchi and Bering seas. This study highlights the need to monitor potentially toxic microalgae in the Arctic and sub-Arctic regions, as well as species of mollusk that may be included in future commercial or subsistence harvests. Highlights: Mollusks collected from the Chukchi and Bering seas were analyzed using LC-MS/MS. PTX2 and STX were detected exclusively in mollusks sampled from the Chukchi Sea. OA and DTX1 were determined regionally in mollusks originated in the Bering Sea. SPX1, YTX, and some analogues occurred in most of samples from both sampling sites. No Azaspiracid 1–3, Gymnodimine and Pinnatoxin G were found in any samples tested.